Distribution and diversity of macrobenthos community in the seagrass ecosystem of Merambong Shoal, Johor, Malaysia - Ahmad Ismail, Khairun Waheeda (2020)
Merambong Shoal seagrass bed is heavily impacted by reclamation activities that has been ongoing since 2014. A monitoring survey was conducted to monitor the diversity and distribution of macrobenthos community structure in this seagrass bed along with its interaction with sediment and macrophytes composition in relation to possible environmental disturbance or habitat alteration caused by the reclamation activities. Three 200 m transects were laid across the Merambong North Stations (MNS) while another two were placed in the Merambong South Stations (MSS). Macrobenthos sediment samples were collected bi-monthly from five transects on the seagrass bed using PVC hand corer from December 2015 to June 2018. Macrophytes composition data was also collected from December 2016 to June 2018 using the same transects. Results showed that there was obvious decline in monthly mean density (6.6 – 14.6 ind per m2) and alteration in the composition of macrobenthos dominant groups inhabiting the seagrass bed compared to other previous studies in the same area. There was also spatial difference in where MNS was recorded to have lower macrobenthos abundance (6.6 – 7.0 ind per m2) as in comparison to MSS (10.6 – 14.6 ind per m2). As according to Bray-Curtis similarity analysis the reclamation activities might also even created two distinctively different structure of macrobenthos communities originated from one shoal. It was recorded that there was significant difference (p<0.05) in silt percentage between different transects where T1, T2 and T3 were found to have higher silt percentage (2.10% - 3.01%) than T4 and T5 (0.96% - 1.12%) suggesting higher sedimentation in this part of the shoal. The reclamation activities have also resulted in spatial differentiation in macrophytes composition between different transects around the seagrass bed. MNS was mainly dominated by opportunistic macroalgae Ulva reticulata while MSS continued to contain higher abundance of seagrass cover. It was recorded that there is significant correlation (p< 0.05) between abundance of major macrobenthos groups abundance with sediment and macrophytes composition. Signs of recovery in the seagrass ecosystem were observed after the excavation of the sand causeway separating MNS and MSS, starting August 2017 onwards where seagrass was observed to recolonize MNS area directly replacing the Ulva reticulata invasion. These results concluded that the reclamation activities might have damaging effects on macrobenthos community in Merambong Shoal which also significantly altered its community structure.